2014
DOI: 10.1038/ng.3154
|View full text |Cite
|
Sign up to set email alerts
|

Common variation in PHACTR1 is associated with susceptibility to cervical artery dissection

Abstract: Cervical artery dissection (CeAD), a mural hematoma in a carotid or vertebral artery, is a major cause of ischemic stroke in young adults although relatively uncommon in the general population (incidence of 2.6/100,000 per year)1. Minor cervical traumas, infection, migraine and hypertension are putative risk factors1–3, and inverse associations with obesity and hypercholesterolemia are described3,4. No confirmed genetic susceptibility factors have been identified using candidate gene approaches5. We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
157
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 201 publications
(167 citation statements)
references
References 52 publications
6
157
0
4
Order By: Relevance
“…11 We confirm a maternal excess of stroke in female probands and extend this finding to a young stroke population. 2,6 Our data may underestimate the true effect of female-tofemale transmission.…”
Section: Discussionsupporting
confidence: 77%
“…11 We confirm a maternal excess of stroke in female probands and extend this finding to a young stroke population. 2,6 Our data may underestimate the true effect of female-tofemale transmission.…”
Section: Discussionsupporting
confidence: 77%
“…The vascular finding is consistent with known co-morbidities and previously reported shared polygenic risk between migraine, stroke and cardiovascular diseases 70,71 . Furthermore, a recent GWA study of Cervical Artery Dissection (CeAD) identified a genome-wide significant association at exactly the same index SNP (rs9349379) as is associated to migraine in the PHACTR1 locus, suggesting the possibility of partially shared genetic components between migraine and CeAD 30 . These results suggest that vascular dysfunction and possibly also other smooth muscle dysfunction likely play roles in migraine pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the genes have previous associations to vascular disease (PHACTR1, 29,30 TGFBR2, 31 [43][44][45] and coronary artery calcification 46 and rs11624776 at ITPK1 with thyroid hormone levels 47 ). Six of the loci harbor genes that are involved in nitric oxide signaling and oxidative stress (REST 48 , GJA1 49 , YAP1 50 , PRDM16 51 , LRP1 52 , and MRVI1 53 ).…”
Section: Supplementary Table 6)mentioning
confidence: 99%
“…RAPGEF2 has been found to be critical for murine embryonic hematopoiesis and to be differentially expressed in pulmonary arterial hypertension (47,48). PHACTR1 plays a role in the reorganization and regulation of the actin cytoskeleton and appears to influence important vascular functions (49,50). MCPH1 is a gene that encodes a DNA damage response protein (23).…”
Section: Original Researchmentioning
confidence: 99%